Reformulasi Materi Al-Mu’rabat berdasarkan I’rab dalam Kitab Jurumiyah - Nafisatul Fuadah (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2024)
This research aims to reformulate al-mu'rabat materials in Jurumiyah book by Sheikh Muhammad Ibn Daud Shonhaji. This research is inseparable from several previous studies which show that students of Arabic are still very difficult to understand the book. This research is included inlibrary research which aims to collect some data and information through various kinds of material data contained in the library in the form of books, scientific journal articles, theses, theses, dissertations and other materials or research relevant to this research, while the data collection technique used in this research is the documentation technique which is carried out by carefully reading the Jurumiyah book by Sheikh Muhammad Ibn Daud Shonhaji then reformulating the al-mu'rabat material in accordance with i'rab. The result of this research is that there are several al-mu'rabat materials in the Jurumiyah book by Sheikh Muhammad Ibn Daud Shonhaji that need to be reclassified based on al-mu'rabat isim that is read rofa' , namely 1) Ististna ' with the letter Illa in the form of Kalam Manfi and Tam. 2) La which does not connect with the isim directly and must be repeated. 3) Munada Mufrod 'Alam and Munada Nakiroh Maqshudah. The results of the reformulation of the meteri al-mu'rabat in the Jurumiyah book by Sheikh Muhammad Ibn Daud Shonhaji are Chapter Marfuat Al-Asma consisting of Fail, Naibul Fail, Mubtada' and Khabar, Tawabi' (Na'at, 'Athaf, Taudik and Badal), Ististna' with the letter Illa in the form of Kalam Manfi and Tam, La which does not connect with the isim directly and must be repeated and Munada Mufrod 'Alam and Munada Nakiroh Maqshudah. The chapter on Manshubat Al-Asma consists of Maf'ul Bihi, Mashdar, Dzorof Zaman and Dzorof Makan, Hal, Tamyiz, (Munada: Munada Nakiroh Ghairu Maqshudah, MunadaMudhof and Munada Syibh Mudhof), Maf'ul Min Ajlih, Maf'ul Ma'ah. The chapter on Mahfudzot Al-Asma or Majrurat Al-Asma consists of Isim that are pronounced Jar because they are preceded by harf jar, because of idhofah and because (Tawabi'). Keywords: Reformulation, Al-Mu'rabat, Nahwu, Jurumiyah